Interleukin-2-Inducible T-Cell Kinase Deficiency Impairs Early Pulmonary Protection Against Mycobacterium tuberculosis Infection - Huang, Lu; Ye, Kaixiong; McGee, Michael C.; Nidetz, Natalie F.; Elmore, Jessica P.; Limper, Candice B.; Southard, Teresa L.; Russell, David G.; August, Avery; Huang, Weishan (Frontiers in Immunology, 2020)
IL-2 inducible T cell kinase (ITK) is a nonreceptor tyrosine kinases highly expressed in T cell lineages and regulates multiple aspects of T cell development and function, mainly through its function downstream of the T cell receptor (TCR). Itk deficiency can lead to CD4 lymphopenia, and EBV-associated lymphoproliferation and recurrent pulmonary infections in humans. However, the role of the ITK signaling pathway in pulmonary responses in active tuberculosis due to Mtb infection is not known. We show here that human lungs with active tuberculosis exhibit altered TCR/ITK signaling, and that Itk deficiency impaired early protection against Mtb in mice, accompanied by defective development of IL-17A-producing gamma/delta T cells in the lungs. These findings have important implications of human genetics associated with susceptibility to Mtb due to altered immune responses, and molecular signals modulating host immunity that controls Mtb activity. Enhancing ITK signaling pathways may be an alternative strategy to target Mtb infection, especially in cases with highly virulent strains in which IL-17A plays an essential protective role.